Strength values of shoulder internal and external rotators in junior tennis players - Vodička, Tomáš (Array, 2018)
Character of modern tennis game in the last decade has become significantly more dynamic, fast and powerful, which brings high strain to joint and muscular system. The aim of this research was to establish strength level of external and internal shoulder rotators, and to compare the competitive tennis players group of boys (TEN, n=10, aged 12-14 years) and boys who did not perform any sport activity at competitive level (CS, n=10, aged 12-14 years) as well as to assess lateral differences in both groups. Using isokinetic dynamometry method (Humac Norm CSMI Stoughton, MA, USA), we tested strength level of external and internal shoulder rotators (180°/s, 300°/s). The TEN and CS group are comparable from the aspects of age, body height and body weight. Comparison of isokinetic strength values in TEN and CS groups proved significantly higher strength level of external and internal rotators in both (dominant and non-dominant) extremities for the TEN group. The lateral difference assessment proved the insignificant difference in external and significant difference in internal rotators in the TEN group, and the insignificant difference in both the external and internal rotators in the CS group. A lower strength level was found in the internal rotators in comparison with the external rotators in both groups (for both the dominant and non-dominant extremity), whereas in the TEN group lower differences between the external and internal rotators of the dominant extremity were proved. Although researches on adult highly skilled tennis players refer to a higher strength level of the upper extremity internal rotators, this fact has not been pronounced in the TEN group. An ideal external/internal rotators̕ ratio in adult players is considered within the interval of 66-75%. Significantly higher values obtained in the TEN group might be attributed to lower age and also lower performance level.